The art of [tomorrowkings] : 2006 /> 2016 - Wood, Ashley, 1971- (San Diego, CA : IDW Publishing, a division of Idea and Design Works, 2016)
"The vibrant and mysterious world of Ashley Wood's Tomorrow Kings comes to life in this collection of art and photography. Documenting the lushly designed Tomorrow Kings figures by 3A alongside the kinetic art that inspired the ideas, this coffee table art book is the ideal addition for any collection of Wood. This premiere North American edition includes new artwork and images, each selected by the artist"--Amazon.com.
Keywords: Robots -- Comic books, strips, etc; Science fiction comic books, strips, etc; Graphic arts; Robots